Multiple Identity : Amerikanische Kunst 1975-1995 aus dem Whitney Museum of American Art. - Adolphs, Volker; Drucker, Johanna; Kuspit, Donald; Ronte, Dieter; Ross, David A.; Schmidt, Karsten; Tsai, Eugenie; Whitney Museum of American Art, New York; Kunstmuseum Bonn (Bonn : Kunstmuseum Bonn, 1997)
Africano, Nicholas ; Andre, Carl ; Aycock, Alice ; Bartlett, Jennifer ; Basquiat, Jean-Michel ; Benglis, Lynda ; Bickerton, Ashley ; Blake, Nayland ; Borofsky, Jonathan ; Burden, Chris ; Cain, Peter ; Chin, Mel ; Colescott, Robert ; Dunham, Carroll ; Durham, Jimmie ; Eisenman, Nicole ; Gallagher, Ellen ; Golub, Leon ; Graves, Nancy ; Halley, Peter ; Hammons, David ; Haring, Keith ; Kelley, Mike ; Komar & Melamid ; Koons, Jeff ; Kruger, Barbara ; Kubota, Shigeko ; LeWitt, Sol ; Levine, Sherrie ; Ligon, Glenn ; Lobe, Robert ; Martin, Agnes ; Mendieta, Ana ; Miller, John ; Morrisroe, Mark ; Murray, Elizabeth ; Opie, Catherine ; Oppenheim, Dennis ; Oursler, Tony ; Pierson, Jack ; Pittman, Larry ; Ray, Charles ; Rhoades, Jason ; Rosler, Martha ; Rothenberg, Susan ; Ruppersberg, Allen ; Saar, Alison ; Salle, David ; Schumann, Christian ; Shapiro, Joel ; Sherman, Cindy ; Thater, Diana ; Tomaselli, Fred ; Weiner, Lawrence ; Williams, Sue
biog., ind. tent., gr. tent. p. 121-137
Duits
Multiple Identity : Amerikanische Kunst 1975-1995 aus dem Whitney Museum of American Art, Kunstmuseum Bonn, 4.6. bis 7.9.1997
boek
Keywords: Amerika; New York